A comparison of epiphytic nematode diversity and assemblages in Corallina turves on British and South Korean coasts across hierarchical spatial scales. (26th June 2019) - Kim, Hyeong-Gi; Hawkins, Lawrence E.; Godbold, Jasmin A.; Maclean, Moira; Oh, Chul-Woong; Rho, Hyun Soo; Hawkins, Stephen J.
Abstract: Cosmopolitan habitat-forming taxa of algae such as the genus Corallina provide an opportunity to compare patterns of biodiversity over wide geographic scales. Nematode assemblages inhabiting Corallina turves were compared between the south coasts of the British Isles and South Korea. A fully nested design was used with three regions in each country, two shores in each region and replicate samples taken from three patches on each shore to compare differences in the taxonomic and biological trait composition of nematode assemblages across scales. A biological traits approach, based on functional diversity of nematodes, was used to make comparisons between countries, among regions, between shores and among patches. The taxonomic and biological trait compositions of nematode assemblages were significantly different across all spatial scales (patches, shores, regions and countries). There is greater variation amongst nematode assemblages at the scale of shore than at other spatial scales. Nematode assemblage structure and functional traits are influenced by the local environmental factors on each shore including sea-surface temperature, the amount of sediment trapped in Corallina spp. and tidal range. The sea-surface temperature and the amount of sediment trapped in Corallina spp. were the predominant factors determining nematode abundance and composition of assemblages and their functional diversity.